Carbonyl‐rich Poly(pyrene‐4, 5, 9, 10‐tetraone Sulfide) as Anode Materials for High‐Performance Li and Na‐Ion Batteries. Issue 14 (10th June 2021) - Li, Kang; Xu, Shufei; Han, Donglai; Si, Zhenjun; Wang, Heng‐guo
Abstract: Organic carbonyl electrode materials are widely employed for alkali metal‐ion secondary batteries in terms of their sustainability, structure designability and abundant resources. As a typical redox‐active organic electrode materials, pyrene‐4, 5, 9, 10‐tetraone (PT) shows high theoretical capacity due to the rich carbonyl active sites. But its electrochemical behavior in secondary batteries still needs further exploration. Herein, PT‐based linear polymers (PPTS) is synthesized with thioether bond as bridging group and then employed as an anode material for lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs). As expected, PPTS shows improved conductivity and insolubility in the non‐aqueous electrolyte. When used as an anode material for LIBs, PPTS delivers a high reversible specific capacity of 697.1 mAh g −1 at 0.1 A g −1 and good rate performance (335.4 mAh g −1 at 1 A g −1 ). Moreover, a reversible specific capacity of 205.2 mAh g −1 at 0.05 A g −1 could be obtained as an anode material for SIBs. Abstract : An aromatic carbonyl compound‐linked linear polymer (PPTS) has been synthesized and applied as an organic anode material for lithium‐ion batteries and sodium‐ion batteries, which exhibits better reversible capacities, good cycling stability and outstanding rate performance compared with the monomer (PT).